Remittances and their Response to Portfolio Variables - Catalina Amuedo-Dorantes; Susan Pozo (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
Using a recent Spanish database on immigrants from all across the globe, we show that remittances respond to differences in macroeconomic conditions at home and abroad. This behavior suggests that immigrants are sophisticated economic optimizers who take advantage of differential returns when accumulating assets. Immigrants remit more when per capita GDP growth rates at home are greater than in Spain, when the home-host real interest-rate differential increases, and when real exchange-rate uncertainty is higher. These patterns differ with ownership of home country assets and with the area of the globe from which immigrants originate, whether it is Africa, the Americas, Europe or Asia. The response of remittances to cross-country differences in portfolio variables suggests that remittances may not be counter-cyclical as often claimed. Hence, paradoxically, while remittances may promote consumption-smoothing at the individual or household level, remittances cannot be relied upon to shore up migrant-sending economies in times of need.
Keywords: 330